The photographic zenithal tube (PZT) of the Neuchâtel Observatory (1954-1982): between improvement and paradigmatic break of time determination - Gressot, Julien; Jeanneret, Romain (My University, 2021)
In the mid-20th century, new technologies deeply changed the practices of astronomical observatories. At the meeting of the International Astronomical Union in Copenhagen in March 1946, a call was made for the installation of photographic zenith tubes (PZT) to study variations in latitude and to improve the accuracy of time determination. To remain a reference in this field, The Neuchâtel Observatory seized the opportunity to update its time service. To acquire a PZT, Edmond Guyot (1900-1963), director of the Neuchâtel institution, started discussions with the US Naval Observatory in Washington to obtain plans for their prototype. In the end, Grubb & Parsons, who works on the PZT of the Greenwich Observatory, was chosen. Used between 1954 and 1982, the instrument is seen as significantly reducing instrumental errors and eliminating the personal equation. To explain the issues involved in the transition from the meridian method to the zenith method, this talk intends to start from the material culture of the scientific instrument confronted with the study of the technical documentation and the archives of the Observatory. The PZT is considered to be the future of astronomy in the middle of the 20th century but is finally quite quickly overtaken by technological innovations with atomic time. We will analyses the role of the PZT, at this period of paradigmatic break-in time determination, and the reasons for its sudden obsolescence.
, International on-line workshop : Observing, sensing, detecting Toward a multi-layered picture of the Universe from historical and epistemological perspectives, Italian Society for the History of Physics and Astronomy (SISFA)
Keywords: PZT; History of scientific instruments; zenith observations; accuracy; history of science and technology